Essa luz é da nossa conta: reforma do Estado, privatização e participação na regulação da energia elétrica no Ceará - Silva, Éden Jenklins Rabelo (2009)
This dissertation is the upshot of a work that surveyed public consultations filed with The Regulating Agency for Delegated Public Services of the State of Ceara (Agencia Reguladora de Serviços Públicos do Estado do Ceará – ARCE) and the Brazilian Electricity Regulatory Agency (Agencia Nacional de Energia Eletrica – ANEEL) related to electrical energy distribution in the period of 2006 to 2008. The research aimed at identifying major problems and current difficulties faced by electric energy’s consumers within the State, considering the context of pos-privatization of the State Electrical Company (Companhia Energetica do Ceara – COELCE) as well as current issues faced by regulating agencies in their job of overseeing distribution of energy in the State. The afore-mentioned analysis was guided by themes such as State reform, decentralization, privatization, regulation, participation as well as by items provided by lecturers on the three public hearings adopted as analysis object. The main point was to identify the potentiality of that participative tool in order to determine whether consumers’ involvement in this process resulted in regulation improvement that could lead to the solution of problems pointed by consumers themselves. Within this framework it was possible to identify problems and agents involved in the process of distribution of energy and the regulation of this activity, while observing as well the complexity of problems that was brought forth by those public hearings which led to the conclusion that it was only due to sheer pressure during the three events, especially in the third session, that some results may modify the trend and lead to issues more closely related to public interest.